The demographic, motivational, learning styles and level of satisfaction profiles of second coursers and regular nursing students in Metro Manila - Conjares, Thelma M.
In recent years, the increased number of nursing students included second coursers, students who have a previous baccalaureate degree, whose learner characteristics have not been fully described. The objectives of this study are : to describe the demographic characteristics of second coursers and regular students in nursing as to age, sex, civil status, presence of children, source of financial support, employment/occupational status, previous degree/s earned, and previous employment/profession; to compare the motivations of second coursers and regular students in taking nursing as a course; to compare the learning styles among second coursers and regular students in nursing using the Grasha-Riechmann Student Learning Style Scales (GRSLSS); to compare the level of satisfaction of second coursers and regular students in their learning environment; to describe the problems or difficulties encountered by nursing students, to correlate selected demographic characteristics of second coursers and regular students to motivation, learning styles and degree of satisfaction in the course. A cross-sectional survey was done using a pilot-tested survey instrument that consisted of four parts: Demographic data; Motivations and problems; GRSLSS; and Level of Student Satisfaction. A total of 443 nursing students from the second to the fourth year level from nine schools in Metro Manila that granted permission for the conduct of the study were surveyed. Second coursers are mostly female, married, with children and hold a job while studying. While majority of them depend on their parents for financial support, many are self-supporting; many also depend on their spouses for financial support. Regular nursing students are also mostly female, single, without children, without work and depend on their parents for financial support. Most of the second coursers surveyed are graduates of business- and health-related courses and have been previously employed in the service and health industries. Both groups of students were motivated to take up nursing primarily for financial or economic reasons. Statistically significant differences in learning styles were found between second coursers and regular nursing students based on the GRSLSS. Both groups have a generally high level of satisfaction with their learning environment. The problems and difficulties of nursing students can be grouped into eight themes and includes financial, academic, teacher-related, peer-related, time management, pressure/stress, fears and anxieties, and other problems. Statistically significant correlation was found between age and the motivation to work abroad, and age and the collaborative learning style among second coursers. Based on the GRSLSS, female regular nursing students tend to be more collaborative and dependent than males. These differences in the learner characteristics of second coursers and regular nursing students should be considered in making instructional decisions in class.